Nonhydroxylated 1-O-acylceramides in vernix caseosa - Harazim, Eva; Vrkoslav, Vladimír; Buděšínský, Miloš; Harazim, Petr; Svoboda, Martin; Plavka, Richard; Bosáková, Zuzana; Cvačka, Josef (Journal of lipid research, 2018)
Vernix caseosa, the waxy substance that coats the skin of newborn babies, has an extremely complex lipid composition. We have explored these lipids and identified nonhydroxylated 1-O-acylceramides (1-O-ENSs) as a new class of lipids in vernix caseosa. These ceramides mostly contain saturated C11-C38 ester-linked (1-O) acyls, saturated C12-C39 amide-linked acyls, and C16-C24 sphingoid bases. Because their fatty acyl chains are frequently branched, numerous molecular species were separable and detectable by HPLC/MS: we found more than 2,300 molecular species, 972 of which were structurally characterized. The most abundant 1-O-ENSs contained straight-chain and branched fatty acyls with 20, 22, 24, or 26 carbons in the 1-O position, 24 or 26 carbons in the N position, and sphingosine. The 1-O-ENSs were isolated using multistep TLC and HPLC and they accounted for 1% of the total lipid extract. The molecular species of 1-O-ENSs were separated on a C18 HPLC column using an acetonitrile/propan-2-ol gradient and detected by APCI-MS, and the structures were elucidated by high-resolution and tandem MS. Medium-polarity 1-O-ENSs likely contribute to the cohesiveness and to the waterproofing and moisturizing properties of vernix caseosa.
Keywords: Mass Spectrometry; novorozenec; lipids; ceramides; lipidy; lipidomics; Magnetic Resonance Spectroscopy; ceramidy; vernix caseosa; Gas Chromatography-Mass Spectrometry; magnetická rezonanční spektroskopie; Chromatography, High Pressure Liquid; hmotnostní spektrometrie; Vernix Caseosa; kůže; Lipids; Ceramides; vysokoúčinná kapalinová chromatografie; hmotnostní spektrometrie s elektrosprejovou ionizací; Spectrometry, Mass, Electrospray Ionization; Skin; mass spectrometry; lidé; plynová chromatografie s hmotnostně spektrometrickou detekcí; Humans; skin; Infant, Newborn